Circ_0057452 sponges miR-7-5p to promote keloid progression through upregulating GAB1. Issue 23 (2nd December 2022) - Zhu, Mengying; Li, Yonglin; Liu, Linbo; Zhai, Xiaomei
ABSTRACT: Increasing evidence has shown that circular RNAs (circRNAs) play critical roles in various diseases, including keloid. The purpose of this study was to investigate the role of circ_0057452 and related action mechanisms during the development of keloid. The expression levels of circ_0057452, microRNA-7-5p (miR-7-5p) and GRB2 associated binding protein 1 (GAB1) mRNA were determined by quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using methylthiazolyldiphenyl-tetrazolium bromide (MTT) and 5-Ethynyl-2'-deoxyuridine (Edu) assays. Flow cytometry analysis was utilized to determine cell cycle distribution and cell apoptosis. Western blot assay was used to measure apoptosis-related, collagen synthesis-related, and GAB1 protein levels. Cell migration and invasion were detected by wound healing assay and transwell assay. The interaction between miR-7-5p and circ_0057452 or GAB1 was confirmed by dual-luciferase reporter, RNA pull-down, and RNA Immunoprecipitation (RIP) assays. Circ_0057452 and GAB1 were upregulated in keloid tissues and keloid fibroblasts (KFs), while miR-7-5p was downregulated. Circ_0057452 knockdown or miR-7-5p overexpression inhibited the proliferation, migration, invasion, and collagen synthesis and induced cell cycle arrest and apoptosis of KFs. MiR-7-5p was targeted by circ_0057452, and its inhibition overturned the effects of circ_0057452 knockdown. In addition, GAB1 was a target of miR-7-5p, and GAB1 upregulation abolished the role of miR-7-5p overexpression and circ_0057452 knockdown in KFs. Circ_0057452 regulated the expression of GAB1 by adsorbing miR-7-5p in KFs. Circ_0057452 knockdown suppressed keloid development by regulating miR-7-5p/GAB1 axis, which might provide a promising therapeutic target for keloid.